Umetnost in politika v partizanski Beli krajini - Gabrič, Aleš (Jezik in slovstvo, 1999)
The paper discusses literary activism and censorship in the Partisan-controlled region of Bela krajina during World War II. Attempts to bridle negative sides of the activism came from artists among Partisans, who cleared up a number of questions in their open discussion with politicians. However, differences remained and even intensified after the war. During the war, artists were not constrained so much by censorship as by self-censorship. Political leaders, rather than by using censorship, exerted their influence by dividing artists into more and less wanted, or even unwanted and unofficially banned. In this categorisation, the main criteria were not artistic but political. Censorship and other intervention by influential politicians in art were during the war less common than either before or after it. There does not seem to have been a real need for that, as the influence of war and political divisions on artists was strongly reflectedin their works anyway, so any call for engaged and propagandistic literature was superfluous.
Keywords: Bela krajina; White Carniola; World War II; druga svetovna vojna; slovenska literarna zgodovina; kultura; culture; politics; politika; umetnost; art; zgodovina; history